2021
DOI: 10.1088/1742-6596/1973/1/012154
|View full text |Cite
|
Sign up to set email alerts
|

Influence of electrical discharge machining parameters by additives Nano [AL2O3] on surface roughness and material removal rate in machining of AISI 304

Abstract: Experimental investigation and optimization of machining parameters in electrical discharge machining (EDM) in terms adding particles Nano-reinforced among the various mechanical processes, the process of manufacturing in electrical discharge machines is one of the most effective and cost-efficient manufacturing processes in the manufacture of stainless steel. It has been dealt with in this article investigate each of operating parameters such as peak current (Ip), pulse on time (Pon) and pulse off time(Poff),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Findings observed that a five g/l concentration of Si was the optimum parameter that produced 13.8 µm thickness of the white layer and 2.76 µm surface roughness. Ibrahim [10], investigated the influence of adding Al2O3 to the dielectric on MRR and SR to machine AISI 304 stainless steel. The results determined the appropriate parameters for machine AISI 304.…”
Section: Introductionmentioning
confidence: 99%
“…Findings observed that a five g/l concentration of Si was the optimum parameter that produced 13.8 µm thickness of the white layer and 2.76 µm surface roughness. Ibrahim [10], investigated the influence of adding Al2O3 to the dielectric on MRR and SR to machine AISI 304 stainless steel. The results determined the appropriate parameters for machine AISI 304.…”
Section: Introductionmentioning
confidence: 99%
“…The process involves the utilization of electrical discharges to erode material from a workpiece, making it a proficient approach for severing hard and brittle materials, which present challenges when subjected to traditional machining methods. The utilization of EDM for producing high-precision parts and components has been extensively adopted by various industries, including aerospace, medical, automotive, and electronics [2,3].…”
Section: Introductionmentioning
confidence: 99%